Indonesian Sovereignty Rights in the Case of Entry of Malaysian DA62 Aircraft G-DVOR into Indonesian Territory - Siregar, El Renova Ed.; Prabandari, Adya Paramita (Indonesian Journal of Aerospace, 2022)
The entry of a DA62 aircraft into Indonesian territory from Malaysia has sparked a debate regarding Indonesia's air sovereignty. Indonesia's action to intercept the aircraft before releasing it back has become an interesting subject of research in air law as issues of air sovereignty have not often been the focus of study. Through an understanding of the Chicago Convention on International Civil Aviation and the United Nations Convention on the Law of the Sea (UNCLOS) 1982, it is hoped that an understanding of this issue can guide Indonesia's actions and policies. The research findings using a normative juridical method suggest that Indonesia has legally justifiable grounds to intercept the Malaysian aircraft, and Indonesia's action in releasing the aircraft is in accordance with Indonesia's principles of international politics. However, in the future, challenges regarding historical territory and other issues related to controversies over peaceful routes and outer limits of maritime boundaries have yet to find a middle ground acceptable to all parties.